2005
DOI: 10.1080/13803390490520328
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Studies of Mild Traumatic Brain Injury: A Meta-Analytic Review of Research Since 1995

Abstract: A meta-analysis conducted by Binder, Rohling and Larrabee established a relationship between mild traumatic brain injury (TBI) and small reductions in cognitive functioning in individuals assessed more than 3 months post-injury. As a follow-up, this study summarized similar research that (1) was published since the previous meta-analysis, and (2) included data collected at any stage post-injury. An extensive literature search revealed 17 suitable studies from which effect sizes were aggregated. The overall eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
204
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(223 citation statements)
references
References 58 publications
16
204
2
1
Order By: Relevance
“…Belanger et al (2005) perPersistent post-concussive syndromeformed a meta-analysis of 39 studies involving 1463 cases of mTBI assessing clinical neuropsychological test findings. Their findings were similar to what has also been described by Binder et al (1997), Frencham et al (2005), and Schretlen & Shapiro (2003), implicating short-term, but not necessarily long-term neuropsychological effects, except for those cases who were in litigation, where either "stable or worsening of cognitive functioning over time (p. 215) was observed." Mooney et al (2005), in a university based rehabilitation service, examined those with "disappointing recoveries" and observed that "in cases of poor recovery after mTBI where compensation or litigation may be a factor, most of the variance in recovery seems to be explained by depression, pain, and symptom invalidity (p. 975) ."…”
Section: Limitations Of Neuropsychological Research To Advance the Fisupporting
confidence: 83%
“…Belanger et al (2005) perPersistent post-concussive syndromeformed a meta-analysis of 39 studies involving 1463 cases of mTBI assessing clinical neuropsychological test findings. Their findings were similar to what has also been described by Binder et al (1997), Frencham et al (2005), and Schretlen & Shapiro (2003), implicating short-term, but not necessarily long-term neuropsychological effects, except for those cases who were in litigation, where either "stable or worsening of cognitive functioning over time (p. 215) was observed." Mooney et al (2005), in a university based rehabilitation service, examined those with "disappointing recoveries" and observed that "in cases of poor recovery after mTBI where compensation or litigation may be a factor, most of the variance in recovery seems to be explained by depression, pain, and symptom invalidity (p. 975) ."…”
Section: Limitations Of Neuropsychological Research To Advance the Fisupporting
confidence: 83%
“…Evidence clearly suggests that, for most people, the cognitive effects of mTBI resolve within days to three months post-injury (for meta-analyses see: Belanger et al, 2005;Frenchman et al, 2005;Schretlen & Shapiro, 2003). Yet, despite generally good long-term prognosis for individuals who experience a mTBI, a subset report the subjective experience of chronic cognitive deficits, especially in attention and memory (e.g., Dikmen, Machamer, Fann, & Temkin, 2010;Hartlage, Durant-Wilson, & Patch, 2001;Binder, Rohling, & Larrabee, 1997;Rimel, Giordani, Barth, Boll, & Jane, 1981).…”
Section: Prognosis and Recoverymentioning
confidence: 99%
“…Post-injury reductions in information processing speed have been identified as the single greatest predictor of neuropsychological functioning during the acute stages of recovery following mTBI (Frenchman, Fox, & Mayberry, 2005). In addition, attention, specifically concentration and divided attention, as well as learning/memory processes, are the primary cognitive symptoms following a concussion/mTBI (APA, 2000).…”
Section: Domains Of Cognitive Functioning Affected By Mtbimentioning
confidence: 99%
“…As described above, these impairments typically resolve within the first three months post-injury (Frencham et al, 2005).…”
Section: Implications Of Traumatic Brain Injurymentioning
confidence: 87%
“…The findings of one meta-analysis support this view for the mild cognitive impairments that often follow mild TBI (Frencham, Fox, & Maybery, 2005). However, the remainder of individuals with mild TBI can go on to develop "persistent cognitive, emotional, behavioral, and physical impairments that extend well into the late (>1 year) period following TBI" (Arciniegas et al, 2005, p. 312).…”
Section: Defining Traumatic Brain Injurymentioning
confidence: 95%